Resveratrol Improves Brain-Gut Axis by Regulation of 5-HT-Dependent Signaling in the Rat Model of Irritable Bowel Syndrome - Yu, Ying-Cong; Li, Jing; Zhang, Meixi; Pan, Jian-Chun; Yu, Ying; Zhang, Jian-Bo; Zheng, Liang; Si, Jian-min; Xu, Ying (Frontiers in Cellular Neuroscience, 2019)
Abstract Irritable bowel syndrome (IBS) is at high risk of co-morbid depression and anxiety, which reduces patients' quality of life and increases the burden of health care costs. However, the pathophysiological mechanisms responsible for IBS still remain unknown. This study investigated the effects of resveratrol on stress-related depression, anxiety, intestinal and visceral dysfunction in rat model of IBS. Rats received chronic acute combining stress (CACS) procedures for 22 days exhibited depression/anxiety-like behavior, visceral hypersensitivity and altered intestinal motility, as measured by the forced swimming, marble bury, abdominal withdrawal reflex and intestinal tract motility tests. These abnormalities were accompanied by reduced 5-HT level in the hippocampus and increased 5-HT expression in the gut (ileum and colon) after CACS. Chronic treatment of IBS rats with resveratrol dose-dependently normalized CACS-induced both central nervous and peripheral dysfunction, which were consistent with its differentially regulating 5-HT contents in the brain and intestine. Pretreatment with the 5-HT1A receptor antagonist NAN-190 hydrobromide (NAN-190) prevented such effects. While sub-threshold of 5-HT1A receptor agonist 8-OH-DPAT potentiated the effects of low dose of resveratrol (10 mg/kg) on CACS-related behavioral abnormalities. Furthermore, resveratrol markedly increased PKA, pCREB and BDNF expression in the hippocampus of IBS rats, while decreased PKA, pCREB and BDNF levels were found in the ileum and colon. These effects were prevented by NAN-190, which were consistent with the behavioral changes. The present results suggested that resveratrol improved anti-IBS-like effects on depression, anxiety, visceral hypersensitivity and intestinal motility abnormalities through regulating 5-HT1A-dependent PKA-CREB-BDNF signaling in the brain-gut axis.